The synergistic effect Pt1-W dual sites as a highly active and durable catalyst for electrochemical methanol oxidation. (10th November 2022) - Awoke, Yohannes Ayele; Tsai, Meng-Che; Adam, Dessalew Berihun; Ayele, Adane Abebe; Yang, Sheng-Chiang; Huang, Wei-Hsiang; Chen, Jeng-Lung; Pao, Chih-Wen; Mou, Chung Yuan; Su, Wei-Nien; Hwang, Bing Joe
Abstract: Downsizing precious metal catalysts such as Pt to the atomic level is considered effective and efficient in the catalysis industry. However, Pt single-atom alone cannot catalyze the MOR (methanol oxidation reaction) due to the requirement of Pt ensemble sites to activate C-O bonds. Herein, we report for the first Pt single atom dispersed on dual doped TiO2 (Pt1 / Ti0.8 W0.2 Nx Oy ) as an effective and durable catalyst towards MOR. It is found that synergy between Pt1 -WO3-x dual-active-sites enables the adsorption and dehydrogenation of methanol. Density functional theory (DFT) calculations reveal that W-site adsorbs methanol molecule and the synergistic cooperation between Pt1 -W dual active sites in Pt1 /Ti0.8 W0.2 Nx Oy contributes to the high catalytic activity, stability, and selectivity. The Pt1 / Ti0.8 W0.2 Nx Oy catalyst displays high MOR performance with a mass activity of 560 mA mg −1 Pt at 0.82 V vs. RHE in an alkaline medium. This activity is 9.3 and 1.3 times higher than the corresponding Pt nanoparticle (2 wt% Pt/ Ti0.8 W0.2 Nx Oy ) and 20% Pt/C catalysts, respectively. The lower Tafel slope (93 mV dec −1 ) and higher diffusion coefficient (1.5×10 −12  cm 2 /s) indicate MOR is faster on Pt1 /Ti0.82 W0.18 Nx Oy than the other catalysts. Furthermore, Pt1 / Ti0.8 W0.2 Nx Oy oxidizes methanol to formate with 90% selectivity, whereas 2 wt% Pt/Ti0.82 W0.18 Nx Oy to formaldehyde with 69% selectivity. Moreover, after 10 h, Pt1 / Ti0.8 W0.2 Nx Oy mass activity decayed only by 7.2%. In contrast, 2 wt% Pt/ Ti0.8 W0.2 Nx Oy and 20% Pt/C exhibited 23% and 43% of activity losses respectively. Graphical abstract: Image, graphical abstract